The Importance of Product Quality, Price Perception and Service Quality in Achieving Customer Satisfaction - Prasetyo, Bayu; Sholichah, Mu'minatus; Adil, Malikul; Soelistya, Djoko; Rosyihuddin, Muhammad (Budapest International Research and Critics University, 2022)
The development of science and technology in an all-digital era and globalization as it is today, especially in the field of telecommunications, information and media where these conditions put demands on companies to create more creative solutions and innovations to provide fulfillment to the people of the Indonesian state and it does not apart from marketing management and marketing concept is all activities in telecommunications companies that are motivated by all company activities to plan marketing to meet customer satisfaction which is the company's goal. All activities with the marketing concept will determine how later the management of the marketing management aspect will ultimately have an impact on customer satisfaction.The purpose of this study is to analyze and find solutions to why customer satisfaction occurs in communication companies, even though attention is given to products, prices and services that have been provided. The following research uses a quantitative approach that has a population of customers and users of new products of telecommunications companies with a sample of 100 respondents, while the data analysis model uses the SPSS program with the results that (1) Product Quality affects Customer Satisfaction; (2) Price Perception has an influence on Customer Satisfaction.; (3) Service Quality has an influence on Customer Satisfaction. (4) Together Product Quality, Price Perception, Service Quality, have a positive and significant influence on Customer Satisfaction,